Into the discomfort zone of decolonising aid: how humanitarian actors can effect change - Marianne Mosebo (Journal of International Humanitarian Action)
Abstract The article explores why the promised changes towards greater more equal power relation in the humanitarian system does not happen despite a general willingness to be part of that change. The articles argues that programmatic actors in INGOs have a role to play in this and have to on the responsibility to do what in within their power to make that change. Inspired by Tim Ingold’s conceptual framework, it provides examples from two suggested change processes, “capacity strengthening initiatives” and “participation” efforts, and why they do not effectuate change, because they are framed in structures, which maintain the status quo. The article argues that INGO actors need to build their response ability so they can work in correspondence with their local and national partners. This means that humanitarian actors have to move out of the comfort zone, which maintains an ineffective and power-unbalanced humanitarian system, and into a zone which may be unsettling and provide some discomfort, but which is inquisitive and open to actual equal participation in the important work of humanitarianism.